Approaching Teaching as a Complex Emotional Experience: The Teacher Professional Development Stages Revisited - Perla Villegas-Torres; M. Martha Lengeling (Universidad Nacional de Colombia, 2021)
Along the evolving teaching journey, teachers experience a series of events that allow them to transition from novice to expert. Throughout the years, such transition has been the object of theories and debates about how this process is carried out, and when it is that teachers move from one stage to the other. This article presents a study of a Mexican teacher of English and examines the professional-developmental stages based on Huberman's (1993) career cycle model. Its aim is to understand the challenges and decisions a teacher may encounter in her or his career. The article shows the realities a teacher faces by exploring the concepts of emotions, identity, socialization, and agency. Moreover, it questions the belief that teachers achieve expertise through accumulating years of practice.